2016
DOI: 10.1002/chem.201604316
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Energy Transfer Efficiency between Ce3+ and Ln3+ Ions (Ln=Tm, Sm, Tb, Dy) by Controlling the Crystal Phase of NaYF4 Nanocrystals

Abstract: NaYF is a superior host matrix to study the luminescence properties of lanthanide (Ln ) ions. Ln ions in hexagonal-phase NaYF (β-phase) nanocrystals (NCs) exhibit strong luminescence via an upconversion process compared to cubic NaYF (α-phase) NCs. However, in Ce /Ln -doped NaYF NCs (Ln=Tm, Tb, Sm, Dy) the α-phase NaYF NCs shows strong luminescence compared to their counterpart β-phase NCs despite the latter being much larger in size. This is attributed to comparatively large overlap between Ce ions emission b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…NaYF 4 exhibits in two polymorphic forms; cubic (α) and hexagonal (β). Our idea is to consider cubic phase NaYF 4 as a host matrix as recently we observed that Ce 3+ → Ln 3+ energy transfer is more efficient in cubic phase NaYF 4 compared to hexagonal NCs …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…NaYF 4 exhibits in two polymorphic forms; cubic (α) and hexagonal (β). Our idea is to consider cubic phase NaYF 4 as a host matrix as recently we observed that Ce 3+ → Ln 3+ energy transfer is more efficient in cubic phase NaYF 4 compared to hexagonal NCs …”
Section: Figurementioning
confidence: 99%
“…Ln 3 + energy transfer is more efficient in cubic phase NaYF 4 compared to hexagonal NCs. [20] In this work, we report the synthesis of citric acid (CA)capped Ce 3 + /Tm 3 + /Mn 2 + doped NaYF 4 nanocrystals (NCs) using am icrowave method. The strong white light emission is the result of combining the blue (Tm 3 + )a nd green-yellow (Mn 2 + )e missions via energy transfer through Ce 3 + ion sensitization (280 nm excitation).…”
mentioning
confidence: 99%
“…However, the Eu 3 + ions cannot be sensitised directly by Ce 3 + ions. [7][8][9] Recently, a good strategy for sensitising Ln 3 + ions in Ln 3 + -doped nanoparticles has been developed. [10][11][12][13][14] The Ln-doped NPs surface functionalised with aromatic organic ligands, these ligand molecules act as a surfactant to control the growth of the NPs and to make colloidal dispersion of the NPs in aqueous and organic media.…”
Section: Introductionmentioning
confidence: 99%
“…The common activator ions for the downshifting process are Eu 3+ , Tb 3+ , while Er 3+ , Tm 3+ ions are for up‐conversion. However, the Eu 3+ ions cannot be sensitised directly by Ce 3+ ions [7–9] …”
Section: Introductionmentioning
confidence: 99%
“…Lanthanides possess unique optical characteristics due to their intra 4f–4f transitions, resulting in color specificity and sharp emission bands. Ln-based NCs demonstrate both Stokes (downshifting, DS) and anti-Stokes (upconversion, UC) emission processes, depending on the sensitizer and activator ions . Ln-based NCs can be excited under UV light (254 or 350 nm) or NIR light (800, 980, and 1550 nm). For example, in the UC process, Er (green and red), Tm (blue), and Ho (green and red) ions serve as activators, with Yb and Nd acting as sensitizers for excitations of wavelengths 980 and 800 nm, respectively .…”
mentioning
confidence: 99%